Programming in scala - Odersky, Martin (Artima, 2012)
Programming in Scala is the definitive book on Scala, the new language for the Java platform that combines the concepts of object-oriented and functional in a unique and powerful tool for developers. Co-authored with designer Scala language, this authoritative book will teach you, one step at a time, the Scala language and the ideas behind it. The book is carefully designed to help you learn. The first chapters give you enough of the basics that you can already start using Scala for simple tasks. The entire book is organized so that each new concept is based on concepts that came before - a series of steps that promises to help you master the Scala language and the important ideas about programming that Scala embodies. A complete tutorial and reference for Scala, this book covers the entire language and important libraries.